ОРГАНІЗАЦІЯ РОБОТИ ЗАКЛАДІВ ВИЩОЇ ОСВІТИ ПІД ЧАС ВОЄННОГО СТАНУ (Innovative professional education, 2022)
The article pays attention to the issue of organization of work of highereducation institutions during martial law; a number of tasks for solving urgentproblems are proposed